Pembelajaran Tatap Muka Terbatas Pasca Pandemi Covid-19 di SMKN 1 Muara Teweh Kabupaten Barito Utara - Mitro Mitro (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2022)
The implementation of limited face-to-face learning is one of the alternatives provided by the government in overcoming various kinds of problems in online learning. The learning process requires a variety of preparations that need to be done in order to facilitate the learning process of students. In addition to the preparation of supporting facilities and infrastructure, the preparation of competencies from educators also needs to be prepared, because educators have an important role in achieving effective and efficient learning. Teachers are required to have the ability to manage learning, including in designing classes so that limited face-to-face learning can run. Teacher creativity is needed because students during the pandemic are always assisted by their parents must return to being independent students. The implementation of limited face-to-face learning at SMKN 1 Muara Teweh, North Barito District has been carried out in stages, namely the Pre-Instructional Stage which is the preparation stage before learning. The Instructional stage is forming study groups, optimizing the media in designing Learning Materials for presenting Teaching Materials. Post-Learning Stage is the stage carried out to evaluate the course of the learning process.